(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
Introduction: The cerebellum is primarily responsible for coordination, balance, and muscle control. Cerebellar infarction or haemorrhage can lead to an acute onset of cerebellar dysfunction. The dysfunction often leads to ataxia, which is defined as impaired coordination of voluntary muscle movements. Case Presentation: A 54-year-old male rickshaw driver presented with difficulties in walking and transferring, as well as multiple episodes of falling. He also experienced challenges with activities of daily living, such as bathing, dressing, and eating, following a cerebrovascular accident around 7 years ago. Intervention: Intervention was given 1.5 hours per day,5 days a week, for 8 weeks. Intervention includes education sessions, static and dynamic balance training, quasi-mobile task, body weight support treadmill training, stair gait training, slope walking, transfer activity, and task-specific training. Outcomes: After the 8 weeks of intervention, the FIM score improved from 83 to 105, the BBS score improved from 26 to 36, and the ISS score increased from 74 to 83. The time taken to complete the 5 Times Sit to Stand Test decreased from 1.26 minutes to 40 seconds, and the number of falls reduced from 3 to 0. Retention of the exercise effect was also seen in followups (1-2 months). Conclusion: A tailor-made, goal-oriented physical therapy intervention including education, counselling sessions, and exercises designed and implemented based on the principles of motor control, motor learning, and neuroplasticity will provide recovery even in chronic ataxic stroke patients.